If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4x + -12) = 8x + -18 Reorder the terms: 8(-12 + 4x) = 8x + -18 (-12 * 8 + 4x * 8) = 8x + -18 (-96 + 32x) = 8x + -18 Reorder the terms: -96 + 32x = -18 + 8x Solving -96 + 32x = -18 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -96 + 32x + -8x = -18 + 8x + -8x Combine like terms: 32x + -8x = 24x -96 + 24x = -18 + 8x + -8x Combine like terms: 8x + -8x = 0 -96 + 24x = -18 + 0 -96 + 24x = -18 Add '96' to each side of the equation. -96 + 96 + 24x = -18 + 96 Combine like terms: -96 + 96 = 0 0 + 24x = -18 + 96 24x = -18 + 96 Combine like terms: -18 + 96 = 78 24x = 78 Divide each side by '24'. x = 3.25 Simplifying x = 3.25
| 9f+7=-8f+24 | | 2x-29=x+2 | | 2x-10=5x+9 | | 0=n^2+60n+1600 | | 2x-27=x+2 | | 8(x+2)=3(x-5)-7(x+3) | | 5p+7+14p+40= | | 3q=3q-3 | | 0=n*2+60n+1600 | | 2x-27+x+2= | | .19-5m=34 | | .75m+3=-12 | | (2x-27)+(x+2)= | | 2.4=-8(.3p+9) | | 6x+13=-51-10x | | 4(x+3)-2(-x+3)=6-x | | y=x^2-6x+10 | | 4(2h+3)=6 | | 16=.33t+8 | | 8b+2=34 | | 9w+3=39 | | .2x+4=9 | | 4x+2+36x+8= | | 5t^2-26tx+5x^2=0 | | 4x+9=-51 | | .333n+6=9 | | 11x-16=72 | | 0.4a=5 | | 14b+9b=65 | | 5x+2x=120 | | 12b^2=4800 | | 3r+2r=25 |